Changed plant and animal life cycles from 1952 to 2000 in the Mediterranean region - Josep Peñuelas; Iolanda Filella; PerE. Comas (Global Change Biology, 2002)
The available data on climate over the past century indicate that the earth is warming. Important biological effects, including changes of plant and animal life cycle events, have already been reported. However, evidence of such effects is still scarce and has been mostly limited to northern latitudes. Here we provide the first long‐term (1952–2000) evidence of altered life cycles for some of the most abundant Mediterranean plants and birds, and one butterfly species. Average annual temperatures in the study area (Cardedeu, NE Spain) have increased by 1.4 °C over the observation period while precipitation remained unchanged. A conservative linear treatment of the data shows that leaves unfold on average 16 days earlier, leaves fall on average 13 days later, and plants flower on average 6 days earlier than in 1952. Fruiting occurs on average 9 days earlier than in 1974. Butterflies appear 11 days earlier, but spring migratory birds arrive 15 days later than in 1952. The stronger changes both in temperature and in phenophases timing occurred in the last 25 years. There are no significant relationships among changes in phenophases and the average date for each phenophase and species. There are not either significant differences among species with different Raunkiaer life‐forms or different origin (native, exotic or agricultural). However, there is a wide range of phenological alterations among the different species, which may alter their competitive ability, and thus, their ecology and conservation, and the structure and functioning of ecosystems. Moreover, the lengthening of plant growing season in this and other northern hemisphere regions may contribute to a global increase in biospheric activity.